Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan dengan Mediasi Kinerja Manajemen di Perusahaan Jasa Transportasi (GOJEK) - Anidia, Tisna; Nurhayati, Aan; Septia, Calista Nur; Akbar, Muhammad Ali (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2026)
This study aims to examine the effect of Service Quality on Customer Satisfaction with the mediation of Management Performance in a transportation service company (Gojek). The research problem addressed is whether service quality has a direct and indirect effect on customer satisfaction, and how the role of quality management contributes to this relationship. Since the population is considered infinite, the sample size was determined using Lemeshow's formula, resulting in 96 respondents. This study uses a quantitative approach with mediation regression analysis based on the method proposed by F. Hayes, involving active users of Gojek services as respondents. The results show that Service Quality significantly influences Customer Satisfaction, both directly and through the mediation of Quality Management Performance. The indirect effect value of 0.5209 with a confidence interval of [0.3889–0.6733] confirms the significance of the mediation. These findings indicate that improving service quality must be supported by an effective management system in order to have a maximal impact on customer satisfaction.